Response due to impulsive force in generalized thermo-microstretch elastic solid - Kumar, Varun; Singh, R. (Zielona Góra: Uniwersytet Zielonogórski)
A two dimensional Cartesian model of a generalized thermo-microstretch elastic solid subjected to impulsive force has been studied. The eigen value approach is employed after applying the Laplace and Fourier transforms on the field equations for L-S and G-L model of the plain strain problem. The integral transforms have been inverted into physical domain numerically and components of normal displacement, normal force stress, couple stress and microstress have been illustrated graphically.
Keywords: thermo-microstretch; eigen value; Laplace transform; Fourier transform; impulsive force